High Performance Organic Electronic Devices Based on a Green Hybrid Dielectric (Adv. Electron. Mater. 10/2021). (11th October 2021) - Tousignant, Mathieu N.; Rice, Nicole A.; Niskanen, Jukka; Richard, Chloé M.; Ritaine, Dialia; Adronov, Alex; Lessard, Benoît H.
Abstract : Green Polyvinyl Alcohol Interfacial crosslinking of green polyvinyl alcohol (PVA) and polycaprolactone (PCL) bilayer dielectric provides a barrier to moisture and improves single walled carbon nanotube‐based device performance. Benoit Lessard and co‐workers report a functionalized PCL which crosslinks with the hydroxy groups of the PVA layer through simple heat treatment, providing a candidate material for high performance disposable transistor applications in article 2100700 .